THA with Use of Patient-Specific Resurfacing Jigs and a Novel Customized Implant Design. Issue 5 (17th May 2022) - Zinner, Matthew; Schroeder, Lennart; Pumilia, Cyrus A.; Lee, Eric K.; Martin, Gregory
Abstract : » Conventional total hip arthroplasty (THA) largely remains an unguided procedure dependent on the ability and experience of the surgeon. New technologies, such as patient-specific instrumentation and robotics, have shown promising results in improving implant positioning, which has the potential to improve patient outcomes. » The use of off-the-shelf (OTS) implant designs, however, limits the success of the technological advances since they are unable to recreate the native anatomy of the joint. The inability to restore femoral offset and version or the presence of implant-related leg-length discrepancies often lead to suboptimal surgical results that increase the risk of dislocation, fractures, and component wear, compromising postoperative functional outcomes and implant longevity. » A customized THA system, whereby the femoral stem is designed to restore patient anatomy, has recently been introduced. The THA system uses computed tomography (CT)-derived 3D imaging to create a custom stem, patient-specific component placement, and patient-specific instrumentation that matches the patient's native anatomy. » The purpose of this article is to provide information on the design and manufacturing process of this new THA implant, to illustrate the associated preoperative planning, and to describe the surgical technique; 3 surgical cases are presented.